Efficient loading of silver nanoparticles on graphene oxide and its antibacterial properties. (4th June 2020) - Wang, Hui; Zhang, Yalei; Xu, Xiaobing; Yang, Feiyao; Li, Ke; Wei, Di; Liu, Zhongfan
Abstract: Graphene oxide contains polyaromatic structure and a variety of oxygen functional groups, which can form π -type metal ion-aromatic or metal ion-oxygen interaction with transition metals, thus it is a promising dispersant and carrier for silver nanoparticles (AgNPs). Herein, silver nanoparticles/reduced graphene oxide (AgNPs/rGO) was fabricated with scalable synthesis method without additional dispersing agent. The mass percent of AgNPs loading on rGO could be adjusted according to the requirement of applications from 1 ∼ 67% of the total weight of AgNPs/rGO with the sizes of AgNPs 10 ∼ 30 nm. AgNPs/rGO exhibited excellent antibacterial activity towards both gram-positive S. aureus and gram-negative E. coli . In addition, AgNPs/rGO could be easily dispersed in liquid silicone rubber, and when the rubber solidified and formed a three-dimensional structure, AgNPs/rGO-silicone rubber has both effective antibacterial property and very low effusion of AgNPs. This composite has potential to be used as a material of bacteriostasis bottles and wound dressings.